2013
DOI: 10.3892/ijo.2013.1952
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine induces cell death in SAS human oral cancer cells through caspase activation-dependent apoptosis and LC3-I and LC3-II activation-dependent autophagy

Abstract: Abstract. Numerous studies have demonstrated that autophagy is associated with cancer development. Thus, agents to induce autophagy could be employed in some cases for the treatment of cancer. Our results showed that tetrandrine significantly decreased the viability of SAS cells in a concentration-and time-dependent manner. Tetrandrine induced nuclear condensation, demonstrated by DAPI staining. The early events in apoptosis analysed by Annexin V/PI staining indicated that the percentage of cells staining posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 50 publications
2
46
1
1
Order By: Relevance
“…LC3 is initially synthesized in an immature form, pro-LC3, which is converted into a proteolytically processed form, LC3-I, and is finally modified into the phosphatidylethanolamine (PE)-conjugated form, LC3-II. The level of LC3-II and ratio of LC3-II/LC3-I is the important markers that is reliably associated with completed autophagosomes [50,51]. In addition to LC3, it is also possible to use p62/SQSTM1 as an autophagy marker, at least in certain settings [52].…”
Section: Discussionmentioning
confidence: 99%
“…LC3 is initially synthesized in an immature form, pro-LC3, which is converted into a proteolytically processed form, LC3-I, and is finally modified into the phosphatidylethanolamine (PE)-conjugated form, LC3-II. The level of LC3-II and ratio of LC3-II/LC3-I is the important markers that is reliably associated with completed autophagosomes [50,51]. In addition to LC3, it is also possible to use p62/SQSTM1 as an autophagy marker, at least in certain settings [52].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is gradually considered as a hot spot owing to its function of cell waste clearance and anti-tumor effects [25]. Beclin-1 and microtubule-associated protein light chain 3 (LC3) were two major markers to detect autophagy [26]. Beclin-1 is the mammalian homolog of Atg6, which plays a central role in the regulation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed a crosstalk between autophagy and apoptosis [39]. However, other studies have indicated that autophagy inhibits apoptosis [40].…”
Section: Discussionmentioning
confidence: 99%